Problematics Violence in Household Reviewed From Viewpoint Criminology and Victimology - Dwi Seno Wijanarko; Fransiska Novita Eleanora (UIR Law Review, 2020)
Domestic violence is an increasingly widespread problem, and is often triggered or caused by a variety of things, but the most prominent is economic problems or primary needs. Perpetrators as people who commit violence can be reviewed why to do it, due to several factors in him, such as the environment, heredity, psychiatric disturbed so that in solving household problems is often done with high emotions and full of inappropriate words spoken to the interlocutor. While the victim as the party suffering due to the treatment given by the perpetrator must also be seen, the perception of the victim as a weak party, the victims here based on the type there are victims who really want themselves to be victims, there are victims who are truly themselves victims, exploited by the perpetrators, where violence there are various forms of physical, psychological, sexual violence and neglect of the household, this is seen when viewed from the perception of criminology and victimization. The research method used is normative juridical that is by tracing the literature and legislation relating to the problem under study. The result is that the perpetrators of domestic violence are seen from the aspect of the perpetrators' responsibilities regarding their age to be able to punish and sanction, the victims see their role when the crime is related to the loss suffered, and the settlement of the household according to the law on the elimination of violence in the household namely number 23 of 2004, namely by preventing the occurrence of criminal acts, protecting victims, providing emergency assistance, assisting the process of determining the application for protection.